Non-malignant Helicobacter pylori-Associated Diseases - Falkeis-Veits, Christina; Vieth, Michael (Springer New York LLC, 2019)
Helicobacter pylori infection of the human stomach is associated with chronic gastritis, peptic ulcer disease or gastric carcinoma, and thus a high burden for the public health systems worldwide. Fortunately, only a small subfraction of up to 15–20% of infected individuals will develop serious complications. Unfortunately, it is not always known upfront, who will be affected by serious diesease outcome. For risk stratifications, it is therefore necessary to establish a common terminology and grading system, that can be applied worldwide to compare population data. The updated Sydney System for classification of gastritis with its semi-quantitative analogue scale is the system, that is currently used worldwide. Additionally, pathologists should always try to classify the etiology of the inflammatory infiltrates in the stomach to instruct the clinicians for choosing a proper treatment regime. Risk factors such as intestinal metaplasia, atrophy and scoring systems to classify these risk factors into a clinical context such as OLGA and OLGIM are discussed. Also, special forms of gastritis like lymphocytic gastritis, autoimmune gastritis and peptic ulcer disease are explained and discussed e.g. how to diagnose and how to treat. Extra-gastric sequelae of H. pylori infections inside and outside the stomach are shown in this chapter as well. Important host and bacterial risk factors such as pathogenicity islands are dicussed to draw a complete landscape around a H. pylori infection, that still can be diagnosed in patients. However, it needs to be noted that some countries have almost no H. pylori infection anymore, while others have still a very high frequency of infections with or without serious complications. The understanding and application of risk assessements may help to save money and quality of life. Extra-gastric H. pylori infections are rarely reported in the literature until today. The pathogenitiy is still under debate, but especially in the bile ducts and gallbladder, several pathological conditions may be also based on H. pylori infection, and will be also discussed.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Atrophic gastritis; Gastritis; Helicobacter pylori; Sydney system